A delayed computer virus model with nonlinear incidence rate. Issue 1 (1st January 2019) - Chu, Yugui; Xia, Wanjun; Wang, Zecheng
Abstract : An Susceptible-Vaccinated-Exposed-Infectious-Recovered computer virus model with nonlinear incidence rate and two delays is proposed and its Hopf bifurcation is investigated. The existence of Hopf bifurcation at the viral equilibrium is established by analyzing its distribution of characteristic values. Moreover, the stability and the direction of the Hopf bifurcation are obtained by using the normal form theory and centre manifold theory. Finally, a numerical simulation is performed to validate the theoretical results obtained in the paper.